Analysis of sustainable practices in micro-enterprises of the industrial sector of the central region of the state of Rio Grande do Sul - Motta, Stéfani Dona; Bianchi, Renata Coradini; Zonatto, Patrinês Aparecida França; Boligon, Juliana Andreia Rudell; Silva, Ana Carolina Cozza Josende da (Revista de Administração da UFSM, 2020)
Nowadays companies are under pressure from the globalized market to have a sustainable, quality and value added attitude. The micro-enterprises along with the ones of small size are the most representative in the world, highlighting the importance of their role in the society according to the Brazilian Support Service for Micro and Small Enterprises - SEBRAE (2017). Therefore, this research aims to analyze the sustainable practices used by microenterprises from the industrial region of the central state of Rio Grande do Sul. To do so, the nature of research is classified as qualitative and quantitative, exploratory, and the methodology used was the multiple case study. The research was applied in five micro-companies of the industrial sector that make up the Metal Centro cluster, through semi-structured interviews with the managers. The obtained data were processed in the software Sphinx Léxica - v5, to aid in the interpretation, after analyzing the quantitative data, the content analysis of the results obtained with the theory approached was performed. .From the research it was evidenced that the micro companies have basic attitudes about sustainable practices, that is, they use those methodologies that are within their reach, because the practices that require a greater degree of dedication, commitment and investment, are not executed. Given this, the results achieved in this research indicate that the development of sustainable practices is not the priority in the business of companies, except in cases of legal norms or government requirements.